2024
DOI: 10.1051/0004-6361/202348142
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar interaction models for the early bolometric light curve of SN 2023ixf

L. Martinez,
M. C. Bersten,
G. Folatelli
et al.

Abstract: Type II supernovae ( show growing evidence of an interaction with circumstellar material (CSM) surrounding their progenitor stars as a consequence of enhanced mass loss during the last years of the progenitor's life, although the exact mechanism is still unknown. We present an analysis of the progenitor mass-loss history of SN 2023ixf, a nearby showing signs of an interaction. First, we calculated the early-time ($<$\,19 days) bolometric light curve for SN 2023ixf based on the integration of the observed fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Zimmerman et al (2024), via an analysis of early time UV spectra obtained of the SN with HST, estimated densities and dimensions of different regimes within the star's CSM. Those authors determined that a higher-density (∼5 × 10 −13 g cm −3 ), confined (2 × 10 14 cm; see also Martinez et al 2024) region of CSM above the stellar photosphere (they estimated the star's radius at ∼5 × 10 13 cm, whereas our estimate is a factor of 2 larger, ∼1 × 10 14 cm; see Section 8) extended the shock breakout. Beyond that the CSM density drops (to 10 −15 g cm −3 ) and continues to gradually decline.…”
Section: Further Thoughtsmentioning
confidence: 57%
See 1 more Smart Citation
“…Zimmerman et al (2024), via an analysis of early time UV spectra obtained of the SN with HST, estimated densities and dimensions of different regimes within the star's CSM. Those authors determined that a higher-density (∼5 × 10 −13 g cm −3 ), confined (2 × 10 14 cm; see also Martinez et al 2024) region of CSM above the stellar photosphere (they estimated the star's radius at ∼5 × 10 13 cm, whereas our estimate is a factor of 2 larger, ∼1 × 10 14 cm; see Section 8) extended the shock breakout. Beyond that the CSM density drops (to 10 −15 g cm −3 ) and continues to gradually decline.…”
Section: Further Thoughtsmentioning
confidence: 57%
“…Following Grefenstette et al (2023), Zimmerman et al (2024) assumed a gas density ∼ 4 × 10 −16 g cm −3 at ∼10 15 cm, whereas we found the dust density to be ∼10 −17 to ∼10 −18 g cm −3 at this radius (R in ); these two density estimates are consistent for a reasonable assumed gas-to-dust ratio of 200. We note that the modeling by Martinez et al (2024) results in a constraint on an extended CSM, at ∼8 × 10 14 cm, which is consistent with the confidence intervals on R in ; however, we posit that the lowerdensity dusty CSM extends well beyond that (see also Li et al 2024). In Figure 15 we show a cartoon schematic of the approximate progenitor CSM geometry, with the asymmetric (Smith et al 2023;Vasylyev et al 2023;Li et al 2024), confined CSM indicated above the photosphere and the inner radius of the simplistically spherical dust shell represented, as well as the range of possible binary orbits; this again illustrates Figure 15.…”
Section: Further Thoughtsmentioning
confidence: 94%
“…The close-by CSM are possibly common for SNe IIP/IIL, but the mass-loss rate derived from their spectra or light curves are far higher than that from their RSG progenitors. For instance, the progenitor mass-loss rate was derived as 10 −3 -10 −2 M e yr −1 from the observations of SN 2023ixf itself (Jacobson-Galán et al 2023;Zhang et al 2023;Bostroem et al 2023;Martinez et al 2024), while they were derived as 10 −5 -10 −6 M e yr −1 from the progenitor images usually taken 10-20 yr before corecollapse. It remains unknown on how the mass loss of RSGs is enhanced in their final years prior to explosion.…”
Section: Introductionmentioning
confidence: 99%